Maturation of early-ripening mandarin as affected by scion and rootstock cultivars in western Santa Catarina, Brazil - Brugnara, Eduardo Cesar (Revista Ceres, 2025)
In Santa Catarina, Brazil, ‘Satsuma Okitsu’ and the ‘common mandarin’ (Citrus deliciosa Ten.) are the widely known mandarin varieties harvested earlier than ‘Ponkan’. This study analyzed and compared the maturation evolution of early maturing mandarins in two rootstocks. The experiment had as treatments combinations of the scion cultivars SCS458 Osvino, Clemenules, Satsuma Okitsu and Mexirica do Rio IAC and the rootstocks ‘Swingle’ and ‘IAC 387 Carrizo’. Fruit were sampled during ripening to evaluate soluble solids (SS), total acidity (TA), ratio (SS/TA), juice content and skin color (CIE Lab parameters and color index - CI). Treatments were compared by analysis of variance and linear and nonlinear modeling. Scions significantly affected the evaluated variables, but no rootstock effect was found. ‘SCS458 Osvino’ showed earlier ratio and, mainly, CI, but its juice content was low in part of the period. ‘Satsuma Okitsu’ and ‘Clemenules’ presented, early, higher CI and ratio than ‘Mexirica do Rio IAC’. In conclusion, the cultivars SCS458 Osvino, Satsuma Okitsu and Clemenules are more precocious in maturation compared to ‘Mexirica do Rio IAC’, and the first is the most precocious in peel maturation.